Retinal Detachment Following Cataract Surgery A Systematic Review and Meta-analysis of Incidence, Preoperative Risk Factors, and Postoperative Complications - Alshammari, Abdulmohsen Jameel (Ophthalmic surgery, lasers & imaging retina, 2024)
Cataract surgery is the most common surgical operation in the developed world, for treating cataracts, currently the leading cause of blindness worldwide. Retinal detachment (RD) is a potentially sight-threatening adverse effect of cataract surgery. The overall RD case numbers are high due to the common practice of cataract surgery. The Medline, Scopus, and Directory of Open Access Journals databases were searched for relevant articles using the keywords (phacoemulsification OR cataract surgery) AND (retinal detachment, detached retina). The included studies involved 5,480,448 patients, where 36,886 had RD (pooled incidence: 0.66 events per 100 patients, 95% CI 0.43 to 1.00). Male patients had significantly higher odds of developing RD than female patients (odds ratio = 1.73, 95% CI 1.68 to 1.78, P < 0.001). The RD incidence rate across locations was not significantly different. RD is one of the most significant complications following cataract surgery. [Ophthalmic Surg Lasers Imaging Retina 2024;55:668-674.]